Trends in surface temperature variability over Mumbai - NAIR , SUSHMA; HOSALIKAR, K.S. (MAUSAM, 2013)
izs{k.kkRed izek.kksa ls HkweaMy ij lrg rkiekuksa esa m".k izo`fRr dk irk pyrk gSA bl 'kks/k i= esa eqacbZ ds vf/kdre vkSj U;wure rkiekuksa dh izo`fRr;ksa dks Li"V fd;k x;k gSA blesa ,d n’kd ls ysdj izfrnu rd ds fofHkUu dkfyd ekiØeksa ij rkieku izo`fRr;ksa dh tk¡p dh xbZ gSA fo"ke ?kVukvksa ds ?kfVr gksus dh vko`fRr esa izo`fRr;ksa ds fy, ekSle ds leku xq.kksa ds rRoksa dh Hkh tk¡p dh xbZ gSA lkekU;r% eqacbZ esa rkieku dh c<+rh gqbZ izo`fRr ikbZ xbZ gS ftlesa U;wure rkiekuksa dh vis{kk vf/kdre rkieku vf/kd ik;k x;k gS rFkk ;g 95 izfr’kr dh fo’oLrrk Lrj ij lkaf[;dh; :i ls egRoiw.kZ gSA tk¡p dh varj&okf"kZd vkSj varjk ekSle ekuksa nksuksa ij ekWulwu iwoZ vkSj ekWulwu _rqvksa dh vis{kk 'khr _rq vkSj ekWulwuksRrj _rqvksa esa m".krk lfgr ekSleh fHkUurk Li"V :i ls vf/kd ns[kh xbZ gSA pje rkieku ds fo’ys"k.k esa ekSleh fHkUurk Hkh Li"Vr% ns[kh xbZ gSA xeZ fnuksa vkSj xeZ jkrksa esa ?kVukvksa dh vko`fRr 'khr_rq vkSj ekWulwuksRrj _rqvksa dh vis{kk ekWulwu iwoZ vkSj ekWulwu _rqvksa esa vf/kd Li"V :i ls ns[kh xbZ gSA lHkh _rqvksa esa nksuksa LVs’kuksa ij fnu vkSj jkr nksuksa ds le; ds rkiekuksa esa larqfyr m".k izo`fRr ikbZ xbZ gS gk¡ykfd ekWulwuksRrj _rq esa lkarkØqt esa ;g fHkUurk lkaf[;dh; :i ls ux.; ikbZ xbZ gSA Observational evidence points to a warming trend in surface temperatures over the globe. This paper focuses on the trends in Maximum and Minimum temperatures over Mumbai. The temperature trends were investigated at different temporal scales from decadal to daily. The seasonal series were also investigated for trends in frequency of occurrences of extreme events. In general an increasing trend is observed over Mumbai, with the increase in Maximum temperatures more than the Minimum temperatures and statistically significant at 95% confidence level. A seasonal distinction is evident with the warming more in the Winter and Post Monsoon seasons as compared to the Pre Monsoon and Monsoon seasons at both the inter-annual and intra-seasonal scales of investigation. The seasonal distinction was also evident in the extreme temperature analysis. The frequency of occurrences in the hot days and hot nights were more pronounced in the Pre Monsoon and Monsoon seasons as compared to the Winter and Post Monsoon seasons. Symmetric warming trend was observed for both the daytime and nighttime temperatures at both the stations in all the seasons though the variations at Santacruz are statistically insignificant in the Post-Monsoon season